‘No one wants to end up on YouTube’: sousveillance and ‘cop-baiting’ in Canadian policing - Huey, Laura (Policing and society, 2024)
Citizen recordings of police-public encounters are increasingly surfacing on social media, especially those in which individuals intentionally create confrontational situations to provoke a desired response from police officers. The latter is a form of, what we term, cop-baiting, driven mainly by the ubiquitous sousveillance of police by citizens. Although the literature has explored how media can impact public perceptions of police and police legitimacy, little research has examined cop-baiting social media content specifically or the impacts of cop-baiting forms of sousveillance. The current study investigates police officers’ perspectives, concerns, and experiences of these phenomena while concurrently exploring the perceived consequences of these on officers and policing, representing a novel departure from previous work. To examine police sousveillance and cop-baiting, we draw on qualitative interviews with over sixty police officers from across Canada who have been involved in the policing of politically contentious events. Most notable among the findings were that officers reported a range of impacts of sousveillance and cop-baiting, including occupational stress, effects on families and loved ones, and professional and reputational implications. It was also uncovered that police sousveillance and cop-baiting could significantly undermine police legitimacy and public trust. The current study concludes with some final thoughts on the meaning of cop-baiting and the problematic nature of this activity, a future research agenda, and considerations for police and policymakers.